PENAMBAHAN ASAM OLEAT TERHADAP Sistem transpor Cu(II) dengan zat pembawa oksin melalui teknik membran cair fasa ruah - Tetra, Olly Norita; -, Zaharasmi; -, Refinel (Universitas Andalas, 2008)
ABSTRACT The removal of Cu(II) from aqueous solutions had been employed throught bulk liquid membrane techniques with arrange the optimization conditions of transport Cu(II) interface system. The optimum conditions of transport were found to be 3.1510-4 M of Cu(II) at pH 3 in the source phase, 17.510-4 M oxine dissolved into chloroform as membrane phase, 0,15 M H2SO4 as acceptor in receiving phase, stirring rate was 340 rpm and it was found that the transport of Cu(II) to receiving phase reached 97.41% during 6 hours. The effect of addition oleat acid 1.57 10-3 M as surfactant in membrane phase resulted a rapidly time of transport Cu(II) to be 3 hours, wherein Cu(II) transported into the receive phase reached 97.83% and remained in feed phase 0%. Keywords: bulk liquid membrane, oxine, oleat acid, Cu(II) )transport